HDL meets triglyceride - Tugce Akcan; Fredric B. Kraemer (Journal of Lipid Research)
Abstract: The study by Liu et al in this issue of the Journal of Lipid Research leverages data from the UK Biobank to explore the impact of HDL-TG on atherosclerotic cardiovascular disease risk. The investigators observed that elevated serum triglyceride levels were associated with reduced HDL particle diameter and with increased HDL-TG. Using observational and Mendelian randomization analyses, HDL-TG levels were independently associated with atherosclerotic cardiovascular disease risk even after adjusting for multiple confounders and other risk factors. The results emphasize the need for a broader evaluation of lipid parameters that extends beyond traditional measurements and suggest that incorporating metrics like HDL-TG could enhance risk stratification.